Treatment oOf Palm Oil Mill Effluent using Combination of Microbial Fuel Cell and Anaerobic Membrane Bioreactor - Kong, Hong Feng (2017)
Membrane fouling is a perennial problem that becomes a limiting step to the extensive application of membrane technology in industry. In order to reduce the fouling propensity, the effect of temperature on anaerobic membrane bioreactors (AnMBRs) which operated under mesophilic and thermophilic regimes was investigated, and they were found to have significant effect on AnMBRs performance. The difference in operational temperatures was associated to the biomass growth rate in the bioreactors. The highest COD removal efficiency was observed in mesophilic condition (45°C) with an average COD removal efficiency of as high as 95.60 ± 0.30%. Despite the excellent performance in removing the organic pollutant, the bioreactors operated at 45°C had the highest filtration resistance compared to others. In order to further improve the filtration performance, the AnMBRs were integrated with microbial fuel cell (MFC) instead of sole AnMBR in treating palm oil mill effluent (POME). The MFC acted as a pretreatment unit prior to AnMBR and it was fed directly with POME. The supernatant from MFC was further treated by AnMBR. Noticeable improvement in filtration performance was observed in the combined system compared to sole AnMBR. Decrease in polysaccharide amount was observed in combined system which in turn suggested that the better filtration performance might be due to the capacity of MFC in reducing the filamentous bacteria where its presence is associated to high extracellular polymeric substances (EPS) secretion.